Bilateral metachronous breast malignancies: Malignant phylloides and invasive breast carcinoma—a case report - Abdullah, Norlia; Rizuana, Iqbal Hussain; Goh, Janice Hui Ling; Lee, Qi Zheng; Md Isa, Nurismah; Md Pauzi, Suria Hayati (Frontiers in Oncology, 2023)
A 57 year old Malay nullipara initially presented with a right breast lump that was increasing in size but defaulted follow-up. Two years later, she developed a contralateral breast lump. She only returned to hospital when the right breast lump had become painful ; 4 years from its onset. The biopsy of the right breast lump was a phylloides tumour and the left breast lump a carcinoma. She had bilateral palpable axillary lymph nodes. She underwent bilateral mastectomy and axillary dissection. The pathology report confirmed the right breast lesion to be a malignant phylloides and the left breast lesion to be a carcinoma (pT3N2). She declined adjuvant treatment. A year post-operatively for the metachronous lesions, she had a right chest wall recurrence with widespread pulmonary metastateses. She was given palliative chemotherapy but succumed several months later.